Autofocusing technologies for whole slide imaging and automated microscopy. Issue 12 (18th September 2020) - Bian, Zichao; Guo, Chengfei; Jiang, Shaowei; Zhu, Jiakai; Wang, Ruihai; Song, Pengming; Zhang, Zibang; Hoshino, Kazunori; Zheng, Guoan
Abstract: Whole slide imaging (WSI) has moved digital pathology closer to diagnostic practice in recent years. Due to the inherent tissue topography variability, accurate autofocusing remains a critical challenge for WSI and automated microscopy systems. The traditional focus map surveying method is limited in its ability to acquire a high degree of focus points while still maintaining high throughput. Real‐time approaches decouple image acquisition from focusing, thus allowing for rapid scanning while maintaining continuous accurate focus. This work reviews the traditional focus map approach and discusses the choice of focus measure for focal plane determination. It also discusses various real‐time autofocusing approaches including reflective‐based triangulation, confocal pinhole detection, low‐coherence interferometry, tilted sensor approach, independent dual sensor scanning, beam splitter array, phase detection, dual‐LED illumination and deep‐learning approaches. The technical concepts, merits and limitations of these methods are explained and compared to those of a traditional WSI system. This review may provide new insights for the development of high‐throughput automated microscopy imaging systems that can be made broadly available and utilizable without loss of capacity. Abstract : A fundamental challenge with automated microscopy and high‐throughput imaging has been the ability to acquire high‐quality, in‐focus images at high speed. This review article discusses different autofocusing approaches for automated microscopy and whole slide imaging (WSI). The technical concepts, merits and limitations of these methods are explained and compared to those of a traditional WSI system.